Multimodal super-resolution optical microscopy using a transition-metal-based probe provides unprecedented capabilities for imaging both nuclear chromatin and mitochondria - Sreedharan,S; Gill,MR; Garcia,E; Saeed,HK; Robinson,D; Byrne,A; Cadby,A; Keyes,TE; Smythe,C; Pellett,P; Bernardino,de la Serna J; Thomas,JA (Journal of the American Chemical Society, 2017)
Detailed studies on the live cell uptake properties of a dinuclear membrane-permeable RuII cell probe show that, at low concentrations, the complex localizes and images mitochondria. At concentrations above ∼20 μM, the complex images nuclear DNA. Because the complex is extremely photostable, has a large Stokes shift, and displays intrinsic subcellular targeting, its compatibility with super-resolution techniques was investigated. It was found to be very well suited to image mitochondria and nuclear chromatin in two color, 2C-SIM, and STED and 3D-STED, both in fixed and live cells. In particular, due to its vastly improved photostability compared to that of conventional SR probes, it can provide images of nuclear DNA at unprecedented resolution.